2019
DOI: 10.1177/1687814019871731
|View full text |Cite
|
Sign up to set email alerts
|

Study on the internal two-phase flow of the inverted-umbrella aerator

Abstract: In order to reveal the gas–liquid two-phase flow pattern of inverted-umbrella aerator, the high-speed photography technology, particle image velocimetry, and Volume of Fluid model are employed to capture the free-surface dynamics and velocity distribution. The Computational Fluid Dynamics simulations are validated by experimental data and the results are in good agreement with experiment. The simulation results of flow field, streamline distribution, velocity distribution, free-surface deformation, and turbule… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Guo [14] mainly used the PBM model to simulate the aeration process, which has high accuracy for a gas-liquid two-phase flow. Liu [15] obtained the real-time flow streamline of the inverted umbrella aerator, using a simulated gas-liquid flow.…”
Section: Text Model and Devicesmentioning
confidence: 99%
See 1 more Smart Citation
“…Guo [14] mainly used the PBM model to simulate the aeration process, which has high accuracy for a gas-liquid two-phase flow. Liu [15] obtained the real-time flow streamline of the inverted umbrella aerator, using a simulated gas-liquid flow.…”
Section: Text Model and Devicesmentioning
confidence: 99%
“…Zhang [13] used single-factor analysis and orthogonal te the optimal working conditions of the aerator. Guo [14] mainly used simulate the aeration process, which has high accuracy for a gas-liqu Liu [15] obtained the real-time flow streamline of the inverted umbre simulated gas-liquid flow.…”
Section: Introductionmentioning
confidence: 99%
“…The sliding grid technique was used to simulate the blade rotation, the internal calculation domain was set to rotate, the rotation speed was 30 rad / s, and the speed of the blade relative to the internal calculation domain was 0. The VOF free liquid surface model is used, and the turbulence model uses the k-ε turbulence standard model [16,17]. The k-ε turbulence model is suitable for turbulent flow at low Reynolds numbers, which can improve the accuracy and credibility of the simulation, especially the vortex Accuracy in turbulent flow [18,19] Use the patch function to set the gas-liquid distribution in the aeration tank.…”
Section: Simulation Experiments Condition Settingmentioning
confidence: 99%
“…The authors found that the transient Eulerian-Eulerian model is better than the VOF model in studying the gas-liquid two-phase flow and bubble dynamic behavior in the ESP. In Liang et al [12], based on computational fluid dynamics, Liang et al used high-speed camera technology and CFD modeling technology to analyze the changes in the free surface of the aeration tank and the evolution of the internal flow field and flow pattern of the inverted umbrella aerator. The high-speed photography results are consistent with the numerical simulation results, which verifies the effectiveness of the CFD model in simulating two-phase flow and lays the foundation for the selection of corresponding methods in this article.…”
Section: Introductionmentioning
confidence: 99%